Infant feeding: a selective review and research needs - J. A. Kusin (Indonesian Pediatric Society, 1988)
Growth faltering starting in infancy can be considered the onset of malnutrition. Infant feeding practices as well as a high prevalence of infectious diseases are causal in this process. While general recommendations on infant feeding are useful as guidelines, it is futile to attempt univorm recommendations as good feeding practices are bound to differ by community. It is felt that the biomedical and social science discipline should investigate the factors influencing infant feeding as well as the consequences of habitual practices on infant health and survival.